The quest for prosperity without inflation - Athanasios Orphanides (European Central Bank (ECB), 2000)
In recent years, activist monetary policy rules responding to inflation and the level of economic activity have been advanced as a means of achieving effective output stabilization without inflation. Advocates of such policies suggest that their flexibility may yield substantial stabilization benefits while avoiding the excesses of overzealous discretionary fine-tuning such as is thought to characterize the experience of the 1960s and 1970s. In this paper, I demonstrate that these conclusions are misguided. To illustrate this fact, I construct a database with data available to policymakers in real time from 1965 to 1993 and, using an estimated model, I perform counterfactual simulations under alternative informational assumptions regarding the knowledge policymakers can reasonably have had about the state of the economy when policy decisions were made. Using realistic informational assumptions overturns findings favoring activist policies in favor of prudent policies that ignore short-run stabilization concerns altogether. The evidence points to misperceptions of the economy's productive capacity as the primary underlying cause of the 1970s inflation and suggests that apparent differences in the framework governing monetary policy decisions during the 1970s compared to the more recent past have been greatly exaggerated.
Keywords: E3; E52; E58; 330